Stimuli-responsive nanomedicine - Zhu, Lin (Singapore : Jenny Stanford Publishing, 2021)
The response to environmental and internal stimuli is one of the basic characteristics of living organisms. Inspired by this natural strategy and fast-developing nanotechnology and materials science, stimuli-responsive nanomedicine has emerged as an active and important field of nanomedicine. This book offers a fundamental and comprehensive overview of stimuli-responsive nanomedicine and compiles and details the recent cutting-edge findings and most impressive achievements in biomedical applications, from a pharmaceutical science perspective, making it the first book of its kind in this field. By providing readers a broad and in-depth coverage of endogenous and exogenous stimuli as well as their applicable nanomedicines, this book is valuable for students, researchers, and educators in biomedical sciences or anyone interested in this burgeoning field.
Overview. pH-responsive nanomedicine for image-guided drug delivery. Enzyme-responsive nanomedicine. Redox-responsive nanomedicine. Hypoxia-responsive nanomedicine. Temperature-responsive nanomedicine. Magnetically responsive nanomedicine. Ultrasound-responsive nanomedicine. Light-triggered drug and gene delivery. Stimuli-responsive liposomes for cancer. Stimuli-responsive nanomedicine for treating non-cancer diseases.
OCLC-licensed vendor bibliographic record.
Keywords: Nanomedicine; Smart materials; MEDICAL / Biotechnology; MEDICAL / Pharmacology; SCIENCE / Nanostructures